A Case report: Brain Metastasis of hepatocellular carcinoma (Nepal Journal of Neuroscience, 2026)
Introduction: Hepatocellular carcinoma (HCC) is the 5th most common malignancy in the world and 2nd most common cause of cancer related deaths. Though extra-hepatic metastases are seen in 64% of patients, metastasis in brain and skull is extremely rare. Case description: A 53-year-old HBsAg positive gentleman with a known Hepatocellular Carcinoma (HCC), receiving radiotherapy and chemotherapy, presented with progressively enlarging swelling over left side of forehead.  Imaging showed a left frontal extradural mass, eroding the underlying skull and exerting a mass effect on the brain. With the primary HCC controlled, differential diagnosis included eosinophilic granuloma, plasmacytoma and intraosseous meningioma were considered. The mass was excised, and biopsy report came out to be metastatic HCC. Postoperative period was uneventful, and radiotherapy of the scalp was added in addition to the continuation of chemotherapy for HCC.Conclusion: Metastasis to skull and brain from primary HCC is a rare condition and we are here reporting such one case.